2020
DOI: 10.1038/s41598-020-62371-7
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Epidemiology of Vancomycin-Resistant Enterococcus faecium (VREfm) in Latin America: Revisiting The Global VRE Population Structure

Abstract: Little is known about the population structure of vancomycin-resistant Enterococcus faecium (VREfm) in Latin America (LATAM). Here, we provide a complete genomic characterization of 55 representative Latin American VREfm recovered from 1998-2015 in 5 countries. The LATAM VREfm population is structured into two main clinical clades without geographical clustering. Using the LAtAM genomes, we reconstructed the global population of VREfm by including 285 genomes from 36 countries spanning from 1946 to 2017. In co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 59 publications
2
27
0
3
Order By: Relevance
“…Our study identified certain extracts of these stem barks as being highly effective in inhibiting bacterial growth of multidrug-resistant strains of E. faecium and S. aureus. Enterococci are mostly commensal non-pathogenic bacteria, present in the GI tract without causing human infections 60 . However, in past decades, E. faecium strains have emerged as one of the most pervasive nosocomial pathogens worldwide that caused numerous outbreaks of serious infections 61,62 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study identified certain extracts of these stem barks as being highly effective in inhibiting bacterial growth of multidrug-resistant strains of E. faecium and S. aureus. Enterococci are mostly commensal non-pathogenic bacteria, present in the GI tract without causing human infections 60 . However, in past decades, E. faecium strains have emerged as one of the most pervasive nosocomial pathogens worldwide that caused numerous outbreaks of serious infections 61,62 .…”
Section: Discussionmentioning
confidence: 99%
“…In the U.S., colonization of hospitalized patients with VRE rapidly increased since the first VRE detection, up to the current endemic levels in many hospitals. On the contrary, in Europe, the prevalence rates in hospitals have remained much lower and only started to increase since the year 2000 [ 17 , 20 ]. The initial reports of VRE in Europe were of organisms that were frequently isolated from healthy people, farm animals, pets, and retail food products, suggesting a large community reservoir [ 14 , 21 ], whereas such a community reservoir seemed absent in the US.…”
Section: Emergence and Dissemination Trends Of Vancomycin-resistanmentioning
confidence: 99%
“…Aunque todos los aislamientos optrA positivos de este estudio fueron E. faecalis resistentes al linezolid, cabe resaltar que un estudio que evaluó la estructura poblacional de E. faecium resistente a la vancomicina (EfmRV) en Latinoamérica ( 35 ) reportó en Colombia un aislamiento de EfmRV portador de optrA pero sensible al linezolid; este fenómeno se ha descrito previamente en China ( 14 ). A la fecha, en la vigilancia nacional solo se recibe aislamientos no sensibles al linezolid para detección de optrA , por lo cual sería necesario evaluar este gen en nuestros aislamientos de Enterococcus spp.…”
Section: Discussionunclassified